Relative and absolute reliability of karate specific aerobic test (ksat) in experienced male athletes - Chaabene, H.; Hachana, Y.; Attia, A.; Mkaouer, B.; Chaabouni, S.; Chamari, K. (Biology of Sport, 2012)
The present investigation was conducted to evaluate the relative and absolute reliability and the minimal detectable change (MDC95%) of the karate specific aerobic test (KSAT) in male karate athletes. Sixteen subjects (age: 22.2±3.7 years, height: 175.7±6.7 cm, body mass: 72.7±7.2 kg and karate experience: 9.2±4.5 years) participated in this study and performed the KSAT twice (test-retest). Reliability of time to exhaustion (TE) was very good, with intraclass correlation coefficient ICC(3.1)>0.90, standard errors of measurement SEM<5% and 95% limits of agreement (LOA) -15.8 ± 74.7 s. The MDC95% of the KSAT was 81.42 s, rated as "satisfactory". The dependent t test showed no significant difference between peak heart rate (HRpeak), peak lactate concentration (Lapeak) and rating of perceived exertion (RPE) between test and retest (P>0.05). Effect size for all variables was dz?0.2, rated as trivial. Thus, when using the present test as a measure of aerobic fitness, a change greater than 9.4% (81.42 s) is necessary to be confident (at the 95% level) that the change in time to exhaustion reflects improvement and exceeds the measurement error. The KSAT is a reliable tool that can be used by practitioners for assessing aerobic fitness in experienced karate athletes.